PENGARUH PER, TATO, ROA DAN KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR BEI - Agha Reyhan Alkahfi; Gatot Nazir Ahmad; Destria Kurnianti (Yayasan Education and Social Center, 2023)
The purpose of this study is to ascertain how the Price Earning Ratio (PER), Total Asset Turnover (TATO), Return on Assets (ROA), and dividend policy affect stock prices. The Price Earning Ratio (PER), Total Assets Turnover (TATO), Return on Assets (ROA), and Dividend Payout Ratio were utilized as the study's independent variables to represent stock performance, firm performance, profitability, and dividend policy, respectively (DPR). The stock price was the study's dependent variable. The study's secondary data source consisted of yearly financial reports from companies. Manufacturing businesses registered on the Indonesia Stock Exchange (IDX) between 2016 and 2019 make up the study's population. 44 firms were employed as samples in this study, and 176 observational items were chosen during the course of 4 years of observations. Purposive sampling approach was employed as the sample strategy in this study. The panel data with the random effect model approach model was employed in this study. The study's findings show that the stock prices are unaffected by the following factors: PER, TATO, profitability (ROA), dividend policy, and stock prices are unaffected by any of these factors